2015
DOI: 10.1016/j.yexmp.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center evaluation of the novel fully-automated PCR-based Idylla™ BRAF Mutation Test on formalin-fixed paraffin-embedded tissue of malignant melanoma

Abstract: The advent of BRAF-targeted therapies led to increased survival in patients with metastatic melanomas harboring a BRAF V600 mutation (implicated in 46-48% of malignant melanomas). The Idylla(™) System (Idylla(™)), i.e., the real-time-PCR-based Idylla(™) BRAF Mutation Test performed on the fully-automated Idylla(™) platform, enables detection of the most frequent BRAF V600 mutations (V600E/E2/D, V600K/R/M) in tumor material within approximately 90 min and with 1% detection limit. Idylla(™) performance was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 22 publications
2
53
0
Order By: Relevance
“…However, KRAS testing is difficult to be implemented in cytopathology laboratories, with little expertise in molecular biology procedures and in-house validation of a laboratory-developed methods. The Idylla KRAS Mutation Test, a rapid and fully automated CE-IVD (European Conformity-In Vitro Diagnostic)-certified test, can represent a valid option for a wider number of pathological centres 16 17 20. The assay has been designed by the manufacturer to process FFPE tissue sections using high-frequency intensity-focused ultrasound technology to obtain amplifiable DNA 16 17 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, KRAS testing is difficult to be implemented in cytopathology laboratories, with little expertise in molecular biology procedures and in-house validation of a laboratory-developed methods. The Idylla KRAS Mutation Test, a rapid and fully automated CE-IVD (European Conformity-In Vitro Diagnostic)-certified test, can represent a valid option for a wider number of pathological centres 16 17 20. The assay has been designed by the manufacturer to process FFPE tissue sections using high-frequency intensity-focused ultrasound technology to obtain amplifiable DNA 16 17 20.…”
Section: Discussionmentioning
confidence: 99%
“…This test, based on allele-specific RT-PCR and performed on the fully automated Idylla platform, provides sample to result functionality, enabling method standardisation even in those diagnostic units without molecular expertise and infrastructure 16 17. The aim of this study was to validate this novel technology on indeterminate pancreatic EUS-FNA.…”
Section: Introductionmentioning
confidence: 99%
“…The Idylla test has a benefit to perform sample processing with a minimum 3 mm 2 area with 20 μm tissue sections and yields results with the least amount of FFPE thyroid samples among the applied methods. Thyroid FFPE samples with less than minimum and more than maximum tissue area as specified in the Idylla instruction could generate BRAF V600E mutation, unlike the previous results on malignant melanoma samples 20. The validated tissue amount for the Idylla BRAF test might be different depending on the tissue types and the presence of pigment.…”
Section: Discussionmentioning
confidence: 72%
“…Their study concluded the Idylla assay and platform enabled very rapid decision making with high sensitivity, large reference range and ease of use even in less experienced laboratories [19]. Likewise, Solassol et al reported similar clinical utility and convenience reporting that the Idylla KRAS Mutation Test afforded simple, highly reliable and rapid routine determination of KRAS mutational status to guide colorectal therapy [20]. …”
Section: Discussionmentioning
confidence: 99%